Efektivitas Unit Pelaksana Teknis Badan dalam Pelayanan Pajak Bumi dan Bangunan Pedesaan dan Perkotaan pada Bapenda Kota Padang - Arraminta, Reyhan; Lanin, Dasman (PUBLICNESS: Journal of Public Administration Studies, 2023)
This research is intended to find out how effective the agency's technical implementation unit (UPTB) is in serving rural and urban land and building taxes (PBB-P2) at Bapenda Padang City. In relation to this study, the researcher used descriptive qualitative methods, and to determine research informants used purposive sampling and snowball sampling techniques. Furthermore, the validity of the data uses the source triangulation technique and will then be analyzed by the researcher. Based on the results of the researchers' findings, the effectiveness of the agency's technical implementation unit (UPTB) in providing rural and urban land and building tax services (PBB-P2) at Bapenda Kota Padang has not been fully effective. The obstacles faced by UPTB in PBB services, especially in changing PBB data, are constrained by the long time to complete data changes because there are many administrative requirements for taxpayers who are lacking. One of the efforts made by UPTB in optimizing PBB services is by utilizing technology, which without having to come to Bapenda or UPTB, the community can check information related to PBB P2 data through an application.